2021
DOI: 10.4081/ejh.2021.3297
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA H19 accelerates tenogenic differentiation by modulating miR-140-5p/VEGFA signaling

Abstract: Rotator cuff tear (RCT) is a common tendon injury, but the mechanisms of tendon healing remain incompletely understood. Elucidating the molecular mechanisms of tenogenic differentiation is essential to develop novel therapeutic strategies in clinical treatment of RCT. The long noncoding RNA H19 plays a regulatory role in tenogenic differentiation and tendon healing, but its detailed mechanism of action remains unknown. To elucidate the role of H19 in tenogenic differentiation and tendon healing, tendon-derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
(50 reference statements)
1
7
0
Order By: Relevance
“…In addition, induction of VEGFA expression by engineered nanoparticles promotes tendon healing. In our previous study, we showed that the long noncoding RNA H19 accelerates differentiation of rat tenocytes by inhibiting miR-140-5p, which leads to upregulation of VEGFA at the lesion site [31]. Expanding on this finding, we demonstrated here that upregulation of VEGFA in exosomes from TDSCs promotes tenocyte development.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In addition, induction of VEGFA expression by engineered nanoparticles promotes tendon healing. In our previous study, we showed that the long noncoding RNA H19 accelerates differentiation of rat tenocytes by inhibiting miR-140-5p, which leads to upregulation of VEGFA at the lesion site [31]. Expanding on this finding, we demonstrated here that upregulation of VEGFA in exosomes from TDSCs promotes tenocyte development.…”
Section: Discussionsupporting
confidence: 63%
“…Rotator cuff tendon tissues were isolated from SD rats as reported previously [31]. Tissues were sliced into small pieces, dispersed, and cultured in 6-well plates with Dulbecco's Modified Eagle Medium (DMEM, #11965092; Gibco, Waltham, MA, USA) supple-mented with 10% fetal bovine serum (FBS, #10100147C, Gibco), 100 U/ml penicillin (#10378016, Gibco), and 100 U/ml streptomycin (#10378016, Gibco) in a humidified 5% CO 2 incubator at 37 °C for 5 days.…”
Section: Isolation Of Rat Tenocytesmentioning
confidence: 99%
“…Subsequently, the differentiation status and the clinical outcomes can be correlated. Based on this, tendon cells can be engineered to specific differentiation status by biochemical or biomechanical means prior to implantation to maximise the therapeutic effect [103,174,175]. These clinical and biological studies will be favourable in providing an insight into the treatment efficacy orchestrated by the differentiation status of tendon cells and also assist in developing a guideline for tendon-derived cell therapy with potential for individual patient customisation (Fig.…”
Section: Defined Differentiation Status Of Tendon Cells For Precise T...mentioning
confidence: 99%
“…TSPCs exhibit spontaneous tenogenic differentiation potentials in vitro (Shin et al 2020 ; Liu et al 2021 ). It has been recently demonstrated that the erroneous differentiation of TSPCs to non-tenocytes is involved in the pathogenesis of chronic tendinopathy (Lui and Chan 2011 ).…”
Section: Resultsmentioning
confidence: 99%